FETD Study of the Wave Propagation in Chiral Metamaterials (Advances in Applied Mathematics and Mechanics, 2020)
In this paper, we propose a finite element time-domain (FETD) method for the Maxwell's equations in chiral metamaterials (CMMs). The time-domain model equations are constructed by the auxiliary differential equations (ADEs) method. The source excitation method entitled total-field and scattered-field (TF/SF) decomposition technique is applied to FETD method for the first time in simulating the propagation of electromagnetic wave in CMMs, based on which a unified ADE-FETD-UPML-TF/SF scheme is proposed to simulate the wave in CMMs. The following properties of CMMs can be observed successfully from the numerical experiments based on our method, i.e., the ability of the polarization rotation, and the negative phase velocity. The amplitude of reflected wave can effectively be controlled by the physical parameters of CMMs.